Increase of Clostridium perfringens in association with Eimeria in haemorrhagic enteritis in Japanese beef cattle. (22nd August 2015) - Kirino, Y.; Tanida, M.; Hasunuma, H.; Kato, T.; Irie, T.; Horii, Y.; Nonaka, N.
Abstract : A coprological survey with detailed clinical observation of naturally occurring haemorrhagic enteritis (HE) cases was conducted to understand the pathophysiology of HE by clarifying the infection status of Eimeria and enteropathogenic bacteria in cattle. Faecal samples from 55 cases of HE and 26 clinically normal animals were collected, and a quantitative examination of Eimeria and potential enteropathogenic bacteria was performed. The number of Eimeria species oocysts per gram of faeces (OPG) exceeded 10, 000 in 69.1 per cent of HE cases with a maximum of 1, 452, 500 OPG and Eimeria zuernii was found to be overwhelmingly dominant. A significant increase in faecal coliform count was observed in HE cases compared with clinically normal animals. Among the animals shedding >10, 000 OPG, 42.9 per cent showed a remarkable increase in C lostridium perfringens abundance (>10 4 CFU/g) in the faeces. In the cases with C. perfringens detected, its abundance was positively correlated with Eimeria OPG and high C. perfringens abundance was always accompanied by high Eimeria OPG. E. zuernii is likely to play a crucial role in massive multiplication of C. perfringens in HE in cattle.